Projek pembelajaran menggunakan teknologi pembuatan komik untuk mendukung proses pembelajaran sains kelas rendah (Master of Elementary Education, University of Riau, 2022)
The goal of this study was to evaluate the efficiency of project assessment in science learning as well as the quality of the development results in that field. The AADIE model was the development model employed in this investigation. Five phase analysis, design, development, implementation and evaluation make up the AADIE model. For the purpose of developing and validating project assessments, the five stages of this development model are utilized as a guide.. Science learning in elementary schools plays an important role in learning science at the next level because initial knowledge students are very influential on students’ interest and tendencies to learn science. In other words, if students’ interest in learning science in elementary school is low, it is likely that at the next level the same thing will happen. In the education unit level curriculum it is explained about the importance of learning science (Ministry of National Education, 2006), one of which is developing curiosity, a positive attitude and awareness of the existence of a relationship that influences each other between science, the environment, technology and society through a scientific inquiry approach. Science lessons are one of the subjects that are important to instill in students because through learning science, students are able to be scientific in solving the problems they face (Rusnadi, 2013). Science learning is expected to be a vehicle for students to learn about themselves and the natural surroundings as well as prospects for further development in applying it in everday life (Susiani, 2013).